De l’intérêt d’une étude sur la vulnérabilité des réseaux routiers et de transport pour la compréhension des vulnérabilités territoriales – Le cas du District Métropolitain de Quito (Équateur) - Florent Demoraes (Unité Mixte de Recherche 8504 Géographie-cités, 2009)
This paper presents a reflection on how relevant it is to assess the vulnerability of the infrastructures on which people’s daily mobility relies in order to understand, at an upper level, the territorial vulnerabilities. Once defined the concepts involved in this analysis and after a brief description of the research framework, the four steps thought process is detailed. The first step was to analyze people’s daily mobility (motivation, trips volume, origin and destination) and the transportation system (offer and network) within the Metropolitan District of Quito (MDQ). This allowed pinpointing in a second step, key elements within road and transportation network referred to as critical infrastructures. The third step was to assess the critical infrastructure vulnerabilities which expose them to disturbances or failures. The fourth step was to identify all the areas which are liable to experiment a reduction of their accessibility due to a loss of critical infrastructures serviceability. This allowed assessing finally through scenarios the spatial backlashes which are likely to occur at the MDQ scale.